Creating impact in citizenship education by transformative research: Indications for professionalisation - Marej, Katarina (JSSE - Journal of Social Science Education, 2020)
Purpose: The article reconsiders and explicates the role of academia within and for society and suggests quality standards for normative research. Approach: The article analyses and discusses transdisciplinary procedures for citizenship education research in democracies. Findings: Paradigmatic decisions concerning ontology, axiology, epistemology, and methodology need to be made consciously and transparent. This professionalisation is necessary to ensure that the requirements of academic knowledge are met. Furthermore, the social responsibility of research needs to be acknowledged and methodologically taken into account. Implications: The article suggests three main quality aspects for normative research: transdisciplinarity, transparency, and reflection. It emphasises the ethical and epistemological challenges of research in democracies. Hence, there has to be a close focus on structures and power during the research in order to not just create any impact, but good impact.